Rapid and label‐free identification of different cancer types based on surface‐enhanced Raman scattering profiles and multivariate statistical analysis. Issue 2 (12th October 2020) - Fang, Yaping; Lin, Taifeng; Zheng, Dawei; Zhu, Yongwei; Wang, Limin; Fu, Yingying; Wang, Huiqin; Wu, Xihao; Zhang, Ping
Abstract: Rapid detection and classification of cancer cells with label‐free and non‐destructive methods are helpful for rapid screening of cancer patients in clinical settings. Here, surface‐enhanced Raman scattering (SERS) was used for rapid, unlabeled, and non‐destructive detection of seven different cell types, including human cancer cells and non‐tumorous cells. Au nanoparticles were used as enhanced substrates and directly added to cell surfaces. The single cellular SERS signals could be easily and stably collected in several minutes, and the cells maintained structural integrity over one hour. Different types of cells had unique Raman phenotypes. By applying multivariate statistical analysis to the Raman phenotypes, the cancer cells and non‐tumorous cells were accurately identified. The high sensitivity enabled this method to discriminate subtle molecular changes in different cell types, and the accuracy reached 81.2% with principal components analysis and linear discriminant analysis. The technique provided a rapid, unlabeled, and non‐destructive method for the detection and identification of various cancer types. Abstract : Herein, single‐cell surface‐enhanced Raman scattering technology was applied for rapid analysis of different cancer types and non‐tumorous ones. The similarities and differences between cancerous Raman phenotypes were analyzed at cellular, subcellular, and molecular levels. This study provided a rapid, accurate, label‐free, and non‐destructive method for the detection and identification of various cancer types.